Increased pre-operative and fewer post-operative home visits yield similar outcomes for total joint replacement patients than traditional home care (Home and Community Care Digest, 2003)
Post-operative home care for patients who have undergone total joint replacement surgery accounts for a considerable portion of Medicare expenditures and, due to an aging population, is expected to increase in future. More cost-efficient home care delivery may be safely achieved through reducing the numbers of post-surgical visits when combined with a pre-operative home care visit.